Phosphorylation of the Hsp90 Co-Chaperone Hop Changes its Conformational Dynamics and Biological Function. Issue 3 (1st February 2023) - Castelli, Matteo; Bhattacharya, Kaushik; Abboud, Ernest; Serapian, Stefano A.; Picard, Didier; Colombo, Giorgio
Graphical abstract: Highlights: Phosphorylation significantly perturbs the conformational landscape of Hop. PTM-modification of Hop dynamics correlates with modified affinity for Hsp90 and Hsp70. Mutants of phosphorylated residue replicate the binding properties of phospho-Hop. Integrating experiments and computation sheds light on mechanisms of PTM regulation. Abstract: The molecular chaperones Hsp90 and Hsp70 and their regulatory co-chaperone Hop play a key role at the crossroads of the folding pathways of numerous client proteins by forming fine-tuned multiprotein complexes. Alterations of the biomolecules involved may functionally impact the chaperone machinery: here, we integrate simulations and experiments to unveil how Hop conformational fitness and interactions can be controlled by the perturbation of just one residue. Specifically, we unveil how mechanisms mediated by Hop residue Y354 control Hop open and closed states, which affect binding of Hsp70/Hsp90. Phosphorylation or mutation of Hop-Y354 are shown to favor structural ensembles that are indeed not optimal for stable interactions with Hsp90 and Hsp70. This disfavors cellular accumulation of the stringent Hsp90 clients glucocorticoid receptor and the viral tyrosine kinase v-Src, with detrimental effects on v-Src activity. Our results show how the post-translational modification of a specific residue in Hop provides a regulation mechanism for the larger chaperone complex of which it is part. In this framework, the effects of one single alteration are amplified at the cellular level through the perturbation of protein-interaction networks.